Responses to elevated daytime air and canopy temperature during panicle development in four rice genotypes under paddy conditions in large field chambers - Pasuquin, Estela M.; Eberbach, Philip L.; Hasegawa, Toshihiro; Lafarge, Tanguy; Harnpichitvitaya, Dome; Wade, Len J. (Elsevier, 2023)
Rising air temperatures have the capacity to impact rice yields in future climates. Studies in large temperature-controlled field chambers were established to examine the responses of four contrasting rice genotypes to elevated daytime temperatures (ET) during reproductive development under paddy conditions. Field chambers were effective in raising mean above-canopy maximum daytime temperatures from 29.9 to 41.1°C during 12 d of ET treatment (68–80 d after emergence, DAE), while increased transpiration under ET resulted in lowering of mean lower-canopy maximum temperature to 33.2°C. Nevertheless, the earliest genotype Vandana encountered a hot spell of 37.0°C at 68–74 DAE in the lower canopy at its late reproductive stage, which exceeded the spikelet sterility threshold of 33.7°C, so its spikelet fertility, grain number and grain yield were reduced under ET. Genotypes differed in the extent of canopy cooling, with less reduction in Vandana and IR64 than in N22 and Takanari. For canopy cooling to be effective, stratification of air layers must occur within the canopy, which was more effective under the shorter and denser canopy of N22 and Takanari (plant height of 70–80 cm) than under IR64 (90–110 cm) and Vandana (115–130 cm). Genotypes with appropriate canopy structures should be chosen for high vapour pressure deficit (VPD) conditions. Both maximum canopy temperature and VPD need to be specified to define the critical threshold for heat tolerance. Takanari was notable for greater leaf area retention and greater leaf photosynthetic capacity due to the maintenance of a higher internal leaf CO2 concentration, which lead to higher spikelet and grain numbers and higher yield potential under ET conditions